Pengaruh komitmen pegawai dan lingkungan kerja fisik terhadap kinerja pegawai di Dinas Perindustrian Dan Perdagangan Kota Jambi - Akbariko Akbariko (Jurnal Dinamika Manajemen, 2019)
Employees or human resources (HR) are vital assets in almost all types of organizations which are the main pillars as well as the driving force of the organization in an effort to realize its vision and mission. The research was conducted at the Department of Industry and Trade of Jambi City. Data were collected through questionnaires which were distributed to 65 people using a Liker scale. The research was conducted using a data analysis tool, namely SPSS version 23. The data testing technique used in this study included validity testing with factor analysis, reliability testing with Cronbach's Alpha. T test and multiple linear regression analysis, to test and prove the research hypothesis. The results of the analysis show that organizational commitment and work environment have a significant positive effect on employee performance.